Peridynamic simulation of two-dimensional axisymmetric pull-out tests. (15th August 2019) - Zhang, Yong; Qiao, Pizhong
Abstract: In this study, a systematic pull-out simulation scheme in the formwork of two dimensional (2D) axisymmetric domain using peridynamics (PD) is presented. An axisymmetric ordinary state-based peridynamic model is used to model the pull-out deformation just like the axisymmetric stress element in the finite element method (FEM). A failure criterion based on the bond energy density is adopted to predict the interfacial debonding, while a new PD contact model in the 2D axisymmetric domain is proposed to simulate the friction sliding during the pull-out process. The PD pull-out simulation scheme based on the respective 2D axisymmetric model, interfacial failure criterion and contact model is quantitatively validated in comparisons with either the FEM or analytical solutions. The whole process of the pull-out test is simulated using the proposed PD scheme, and the influences of both the interfacial fracture toughness and friction coefficient on the bond-slip behavior are investigated. The developed PD pull-out modeling scheme is capable of effectively simulating the pull-out tests and predicting the bond-slip behavior.